The British general election of 2001 - Butler, David 1924-; Kavanagh, Dennis 1941- (Palgrave, 2002)
The 16th book in the renowned Nuffield series of election studies covers the Labour victory in the general election of 2001. The background, the campaign, the results and the consequences of the Labour victory are all examined.
Keywords: Great Britain - Parliament - Elections, 2001; Geschichte 2001; Lagerhuis; Verkiezingen; Elections -- Great Britain; Parlamentswahl; Great Britain - Politics and government - 1997-; Großbritannien